Discrimination learning in oxycodone-treated nonhuman primates. (1st February 2020) - Withey, Sarah L.; Doyle, Rachel J.; Porter, Erica N.; Bergman, Jack; Kangas, Brian D.
Highlights: Discrimination learning was assessed during three conditions of opioid exposure. Learning was not affected by self-administered oxycodone. Learning was impaired during withdrawal via naltrexone and abrupt discontinuation. Impairment of learning was concordant with autonomic signs of opioid withdrawal. Abstract: Background: Prescription opioid abuse continues to be a public health concern of epidemic proportions. Notwithstanding the extensive literature regarding opioid action, there has been little systematic research regarding the effects of opioid dependence and withdrawal on aspects of cognition-related behavior in laboratory animals. The present studies examined the effects of the prescription opioid oxycodone on learning processes in nonhuman primates. Methods: The ability of subjects to repeatedly learn novel touchscreen-based visual discriminations was examined during three conditions of opioid exposure. Discrimination learning was examined, first, during oxycodone self-administration (3-hr sessions, 0.1 mg/kg/injection) and, next, during non-contingent chronic treatment with oxycodone (10 mg/kg/day). Finally, discrimination learning was re-examined during antagonist-precipitated opioid withdrawal (0.001-0.1 mg/kg naltrexone) and, subsequently, following abrupt discontinuation of oxycodone treatment. Results: Although motoric behavior was disrupted by oxycodone, neither the development of discrimination learning nor steady-state performance were impaired following oxycodone self-administration or during non-contingent chronic oxycodone treatment. However, discrimination learning was substantially impaired during oxycodone withdrawal, whether elicited by naltrexone or by abrupt oxycodone discontinuation. Moreover, these learning impairments were concordant with autonomic signs of opioid withdrawal. Conclusions: Taken together, the present studies indicate that impairment of learning processes can accompany the unconditioned signs of opioid withdrawal.